In transition: current health challenges and priorities in Sudan - Mark R Johnson; Esmita Charani; Aubrey J Cunnington; AlaEldin H A Yousif; Mohammed Seed Ahmed; Ammar E M Ahmed; Souad Babiker; Shahinaz Badri; Wouter Buytaert; Michael A Crawford; Mustafa I Elbashir; Kamal Elhag; et al. (BMJ Global Health)
A recent symposium and workshop in Khartoum, the capital of the Republic of Sudan, brought together broad expertise from three universities to address the current burden of communicable and non-communicable diseases facing the Sudanese healthcare system. These meetings identified common challenges that impact the burden of diseases in the country, most notably gaps in data and infrastructure which are essential to inform and deliver effective interventions. Non-communicable diseases, including obesity, type 2 diabetes, renal disease and cancer are increasing dramatically, contributing to multimorbidity. At the same time, progress against communicable diseases has been slow, and the burden of chronic and endemic infections remains considerable, with parasitic diseases (such as malaria, leishmaniasis and schistosomiasis) causing substantial morbidity and mortality. Antimicrobial resistance has become a major threat throughout the healthcare system, with an emerging impact on maternal, neonatal and paediatric populations. Meanwhile, malnutrition, micronutrient deficiency and poor perinatal outcomes remain common and contribute to a lifelong burden of disease. These challenges echo the United Nations (UN) sustainable development goals and concentrating on them in a unified strategy will be necessary to address the national burden of disease. At a time when the country is going through societal and political transition, we draw focus on the country and the need for resolution of its healthcare needs.